Epistemology and methodology of urban cultural tourism: the case of the artistic sociology of mobile cultures and tourism communication in urban social networks - Andrade, Pedro de (2018)
The epistemological, theoretical and methodological debates that aim at scientific credibility, cannot ignore the corresponding application to the social fabric. Conversely, action should always inform reflection. This article rationally demonstrates and sensorialy exhibits the following: one of the sociological genres, Artistic Sociology, transports sociology and its scientific language, from the academia to creative extension activities such as the exhibition of sociological knowledge within urban public space, for example in the case of the art gallery. In the same way, artistic knowledge and language should contaminate sociological discussion through an innovative sensibility. This is possible through the insertion, within a sociological text, not only of images from an art exhibition, presented as ‘Figures’ (1,2 ... n). In addition, the art exhibition itself can be understood as a social and sociological configuration that is an organic part of the very body of the traditional sociological text. Thus, a profound hybridization of knowledge is sought, which can enrich, but also subvert, both sociological debates and art exhibitions. This purpose is accomplished here by several interconnected means: an epistemological approach between Artistic Sociology and Hybridogy; the theoretical problematization of mobile cultures; the empirical field work in the context of urban communication at City 3.0 and tourism communication in the context of Tourism 3.0; and the exhibition ‘New Art Fest’17, as the field for the application of innovative sociological and artistic methodological approaches. A first step was Sociological Exibition on Tourism 3.0 / Cidade 3.0, that demonstrated and showed the urban and travel knowledge, within the space of the art gallery. In a second phase, this knowledge tested through the exhibition audience, is reintroduced in a scientific journal article. Such a double research movement hybridizes and confronts, in both originary and original forms, scientific and artistic knowledge and practice.